Characterization of Autozygosity in Pigs in Three-Way Crossbreeding - Ganteil, Audrey; Rodriguez-Ramilo, Silvia T.; Ligonesche, Bruno; Larzul, Catherine (Frontiers in Genetics, 2021)
Crossbreeding in livestock can be used to increase genetic diversity. The resulting increase in variability is related to the heterozygosity of the crossbred animal. The evolution of diversity during crossbreeding can be assessed using genomic data. The objective of this study was to describe patterns of runs of homozygosity (ROH) in animals resulting from three-way crossbreeding, from parental pure lines and in their crossbred offspring. The crossbreeding scheme consisted in a first crossbreeding Pietrain boars and Large White sows, after which the offspring of the Pietrain x Large White were crossed with Duroc boars. The offspring of the second crossbreeding are called G0, the offspring of G0 boars and G0 sows are called G1. All the animals were genotyped using the Illumina SNP60 porcine chip. After filtering analyses were performed with 2,336 animals and 48,579 autosomal SNP. The mean ROH-based inbreeding coefficients were shown to be 0.27 ± 0.05, 0.23 ± 0.04 and 0.26 ± 0.04 for Duroc, Large White and Pietrain, respectively. ROH were detected in the Pietrain x Large White crossbred but the homozygous segments were fewer and smaller than in their parents. Similar results were obtained in the G0 crossbred. However, in the G1 crossbreds the number and the size of ROH were higher than in G0 parents. Similar ROH hotspots were detected on SSC1, SSC4, SSC7, SSC9, SSC13, SSC14 and SSC15 in both G0 and G1 animals. Long ROH, (>16 Mb) were observed in G1 animals, suggesting regions with low recombination rates. The conservation of these homozygous segments in the three crossbred populations means that some haplotypes were shared between parental breeds. Gene annotation in ROH hotspots in G0 animals identified genes related to production traits including carcass composition and reproduction. These findings advance our understanding of how to manage genetic diversity in crossbred populations.